3-dimensional time-domain full-wave analysis of optical array antennas - Oswald, Benedikt; Fomins, Aleksejs; Fallahi, Arya; Leidenberger, Patrick; Bastian, Peter (Journal of computational and theoretical nanoscience, 2011)
We report on the 3-dimensional full-wave analysis of optical array antennas that employ a dipole element as the fundamental building block. We use a finite element time domain (FETD) method discretized on unstructured tetrahedral grids in order to efficiently resolve the geometry which - has a wide range of characteristic length scales, from the nanometer to the micrometer range. Such devices are useful in a number of applications in order to convert propagating electromagnetic energy into localized energy which is concentrated within a spot whose dimension is significantly - smaller than the wavelength. This capability is especially useful for field emitter arrays (FEA) used in novel, ultra-low emittance photocathodes. The antenna elements are modeled with gold metallic properties in the optical region of the electromagnetic spectrum. There, gold is a dispersive - dielectric material and desribed with a Drude dielectric material model. To support the validity of our analysis we numerically analyze electromagnetic problems that can be solved analytically, thus benchmarking the algorithm. We then computationally analyze a single dipole element - in free space and a logarithmically periodic array of dipoles, similar to the concept of the Yagi-Uda array antenna in the microwave region. We demonstrate the existence of resonant modes on the dipole rod elements. Eventually, we comment on further development work.
Gesehen am 13.10.2022